Port site Infection in laparoscopic cholecystectomy in a teriary care hospital – a retrospective study (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Port site infection(PSI) in laparoscopic surgery is not very uncommon. The main aim of this study was to assess the causes of port site infection and its management. This retrospective descriptive study was conducted on 48 patients from March 2019 to December 2020 who develop port site infection after laparoscopic cholecystectomies. Operation notes were analyzed; and swabs were taken for culture & sensitivity. Exploration and wound debride- ment with excisional biopsies were done under local anesthesia for all patients. All patients were followed-up for one year postoperatively. Factors as gender, site of infected port, types of microorganism, acute versus chronic cholecystitis, type of infection (superficial or deep infection) and intraoperative spillage of stones, bile or pus were analyzed . Age of the patients ranged from 15 years to 60 years and the mean age was 32.4 years. The female to male ratio is 2.2:1. Among the subjects, 56.25% patients suffered from acute and 43.75% suffered from chronic cholecystitis. 35.42% had a history of spillage of bile or stones in the abdomen. Considering the site of infection, 33.33% had only umbilical port site infection, 18.75% had only epigastric port infection and 47.92% had multiple port infection. 58.33% suffered from superficial infection and others had deep site infections. Histopathology reports showed granulomatous infection in case of 37.5% patients. So, special consideration should be taken in chronic deep surgical site infection as Mycobacterium tuberculosis could be the cause.BSMMU J 2021; 14(4): 99-103